СПІВВІДНОШЕННЯ ЖИВОЇ ТА МЕРТВОЇ КОМПОНЕНТИ СУСПЕНЗІЇ В КУЛЬТУРІ МІКРОВОДОРОСТЕЙ ЗАЛЕЖНО ВІД СТАДІЇ РОСТУ І ПРИ РІЗНОМУ ОСВІТЛЕННІ - Соломонова, К. С.; Акімов, А. І. (Marine Ecological Journal, 2023)
The suspensions have been studied in cultures of planktonic algae, at the different light and densities, using flow cytometry. The weakly fluorescing component along with algae cells is also present in cultures, the particles of which are the product of dying algae and cells lysis (PIS - photosynthetically inactive suspension). The volume fraction of this particulate matter under favorable growth conditions is 1 – 2 % of the total biomass of algae species with rigid silicon - or cellulose membrane (Phaeodactylum tricornutum and Chlorella vulgaris suboblonga), and does not exceed 0.5 % of the populations of cells Isochrysis galbana, surrounded by the cytoplasmic membrane. In the stationary phase of growth, as well as at high light intensities, the percentage of PIS is increased to 10 – 20 % for Chlorella vulgaris suboblonga and Phaeodactylum tricornutum. For Synechococcus sp. and Isochrysis galbana accumulation of PIS is much less, even with intensive cell lysis that indicating about rapid disintegration and dissolution of fragments cells destroyed. Increasing of PIS share is shown in the long-term steady-state, probably due to the high density culture, and don not with the deficit of mineral nutrition. The particle size of PIS (Phaeodactylum tricornutum) varies widely, from a value exceeding the size of the cells themselves to particles of less than 1 mkm3. The part of small faction in the total volume of particulate matter was maximal with the growth at low light, while at 900 mkE·m-2·c-1 was increased the part of fractions with volume from 10 to 50 mkm3.